(untitled) (Eurasian Journal of Ecology, 2021)
Wild migratory birds are a major contributor to the epidemic outbreaks of West Nile Fever (WNF). WNF acquired particular relevance after many large epidemic outbreaks that took place in the late 90s in some countries in Europe, the Middle East, and the United States. These events were characterized by a high proportion of cases with lesions of the central nervous system (in the form of meningitis and encephalitis) and the mortality rate reached 10%. WNF belongs to the Flaviviridae family, the Flavivirus genus, and is part of the antigenic complex of Japanese encephalitis, to which the viruses Alfai, Katsi- pakore, Koutango, Usutu, Japanese encephalitis, St. Louis encephalitis, and the Murray Valley belong. Following the classification of microorganisms pathogenic for humans, WNF belongs to the II group of pathogenicity. In this regard, in the territory of the Republic of Kazakhstan, monitoring of reservoirs of the West Nile virus among wild birds is carried out. We used 230 samples of cloacal washings from wild birds of Sorbulak Lake in Almaty region, small lakes in North Kazakhstan region, ornithological station “Shakpak” in Zhambyl region. West Nile virus was detected in two samples from wild birds of the families Hirun- dinidae and Sylviidae, respectively, from barn swallows (Hirundo rustica) and chiffchaffs (Phylloscopus collybitus), living in the vicinity of the Shakpak ornithological station of Zhambyl region. Biological samples from barn swallows (Hirundo rustica) and chiffchaffs (Phylloscopus collybitus) tested positive for West Nile virus by RT-PCR. Key words: West Nile fever, arbovirus, wild birds, PCR, RNA.